Comparison of corneal endothelial cell count and intraocular pressure in pure-dispersive and dispersive-cohesive viscoelastic protection in phacoemulsification surgery - Agung Nugroho; R Haryo Yudono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
There are so many aspects should be regarded when use viscoelastic device during phacoemulsification surgery. The advantages and disadvantages of pure-dispersive viscoelastic and dispersive-cohesive viscoelastic always require more our attention to use it conveniently. The purpose of the study was to compare between pure-dispersive viscoelastic versus dispersive-cohesive viscoelastic in phacoemulsification surgery in that of corneal endothelial cell count and intraocular pressure (IOP) change. This was a cross-sectional study involving 41 eligible patients who underwent phacoemulsification surgery by single operator. Data including characteristics of cataract patients, corneal endothelial cell count and IOP were taken before and after surgery. Data of characteristics of cataract patients were reported descriptively and compared using Anova and t-test. The mean change in corneal endothelial cell count on pure-dispersive viscoelastic group (71.99±71.20 cells/mm²) was lower than that on the dispersive-cohesive viscoelastic group (117.62±78.29 cells/mm²). However, it was not significantly different. The mean change in IOP on pure-dispersive viscoelastic group (0.75±1.626 mmHg) was significantly lower than that on dispersive-cohesive viscoelastic group (1.90±0.995 mmHg) (p=0.000). In conclusion, the increase of IOP in dispersive-cohesive viscoelastic group is higher than that on pure-dispersive viscoelastic group. However, there is no significant difference of the mean change in corneal endothelial cell on the both groups.